GENERALIZED CHARACTERISTICS TYPES OF EXCHANGE TRADING STRATEGIES - KARPENKO, VITALII (Herald of Khmelnytskyi National University. Economic sciences, 2021)
It has been determined that online trading is associated with a significant degree of risk, which can be reduced through a thorough and systematic approach to the choice of exchange trading strategies. The strategy (system) of exchange trading is a personal trading rules that take into account the market situation, knowledge and understanding of the trader of this situation, as well as the trader’s wishes regarding the profitability of trading, taking into account the risks. Trading systems based on technical analysis of stock charts are considered: trend (based on the assumption that the price will rise or fall according to market trends), flat (assumes that prices change within a corridor that has clearly defined borders, supported by levels of resistance or support), counter-trend (involves determining the turning point of the price movement), trading on forex patterns (involves determining the figures of graphical analysis of stock charts, resulting in, according to statistics, there is a high probability predict price movements), wave analysis (assumes that market behavior depends on the psychology of participants, which is expressed in the impulsiveness of behavior), breakthrough volatility (assumes that a significant event is the actual exit of the price from the established channel, creating opportunities for trends), session trade (involves work in the market within a specific trade session), trading at Fibonacci levels (assumes that the price should create adjustments to the trend, reflecting the special levels, which are based on the numerical sequence of Fibonacci), scalping (provides trading within the trading day and is characterized by small levels of take profits and relatively large levels of stop-losses) and universal (provide a different combination of the above systems depending on the preferences and experience of the trader). It is concluded that all types of trading systems can be profitable, but first of all it all depends on the knowledge and skills of the person who carries out trading operations.